Comparison of aesthetic perception and acceptability of silver diamine fluoride staining between Spanish and Italian parents - Maria Chiara Cappiello; Ana Veloso Durán; Yasmi Ornelas Crystal; Simone Bagattoni; Francisco Guinot Jimeno (Scientific Reports)
Abstract Assessing parental aesthetic acceptability of Silver Diamine Fluoride (SDF) staining is crucial for its potential implementation in paediatric dentistry in different regions. This study aimed to compare aesthetic perceptions and acceptance of SDF staining between Spanish and Italian parents, and assess weather acceptability is influenced by location, child’s cooperation, or demographic background. A cross-sectional comparative study was conducted among Spanish and Italian parents at three university dental clinics, using a validated Italian version of the questionnaire “Parental perceptions of Silver Diamine Fluoride Dental Color Changes”. 264 Spanish and 234 Italian parents participated in the survey. 41.8% of Spanish parents, compared to 65.4% of Italians, considered staining on posterior teeth acceptable (p < 0.001). 17.2% of Spaniards rated anterior teeth acceptable, versus 19.3% of Italians (p < 0.001). Italian parents showed increased acceptability as child’s cooperation decreased. Acceptability levels in Spain remained more homogeneous, despite linear mixed model identifying a significant increase in acceptability scores from ‘collaboration’ to ‘non-collaboration’ scenario. Spanish and Italian parents found SDF staining on posterior teeth more acceptable than on anterior regions. Level of acceptance increased with child’s uncooperative behavior. Spanish parents generally demonstrated a lower acceptance of SDF pigmentation compared to Italians. Trial registration: NCT, NCT06384326. Registered 21 April 2024, https://clinicaltrials.gov/study/NCT06384326